Determinan Kematian Neonatal di RSUD Sultan Imanudin Pangkalan Bun - Riyanti Riyanti; Legawati Legawati (Jurnal Surya Medika (JSM), 2018)
Efforts to reduce neonatal mortality are done through various efforts in every healthcare setting. Neonatal deaths are caused by various factors, either directly or indirectly. This study aims to determine the cause of neonatal death. The approach used in this research is analytic observational and Cross-Sectional design. The population in this study is all neonatal deaths in RSUD Sultan Imanudin Pangkalan Bun. The sample of research is 103 people. Univariate analyzes were performed with frequency distribution, for bivariate analysis of factors Age of mother, education, occupation, parity, place of birth, the status of the referral, birth attendant and cause of death using chi-square (x2). The results showed that neonatal mortality occurred in the early neonate group 82 people (79.6%). Bivariate analysis showed that parity and cause factor (p = 0,001) showed significant influence on neonatal mortality. Conclusions of the study resulted in parity and direct or indirect causes of neonatal death.